PEMANFAATAN BEKICOT SAWAH (TUTUT) SEBAGAI SUPLEMENTASI PAKAN ITIK UNTUK PENINGKATAN PRODUKTIVITAS ITIK PETELUR DI DESA SIMOREJO-BOJONEGORO - Supartini, Nonok; Darmawan, Hariadi (BUANA SAINS, 2016)
The aim of this research are (1) to know the best composition of snail as duck’s feed supplementation with bran and parcher rice;